Synthesis of polysubstituted 1,4-dihydropyridines via three-component reaction - Balalaie, Saeed; Baoosi, Leila; Tahoori, Fatemeh; Rominger, Frank; Bijanzadeh, Hamid Reza (Tetrahedron, 2012)
An efficient one-pot synthesis of novel N-substituted 1,4-dihydropyridine derivatives via a three-component reaction of primary amines, dialkyl acetylenedicarboxylates, and methyl (arylmethylidene) pyruvates has been reported. The reaction is performed using ZnCl2 (40 mol %) in dichloroethane in good to high yields through a domino Michael/cyclization sequence. Notably, the ready availability of the starting materials, high bond-forming efficiency, good to high yields and the high level of practicability of the reaction and work up make this approach an attractive complementary method for access to N-substituted 1,4-dihydropyridines.